2018
DOI: 10.1158/1535-7163.mct-17-0945
|View full text |Cite
|
Sign up to set email alerts
|

Plk1 Inhibition Enhances the Efficacy of BET Epigenetic Reader Blockade in Castration-Resistant Prostate Cancer

Abstract: Polo-like kinase 1 (Plk1), a crucial regulator of cell-cycle progression, is overexpressed in multiple types of cancers and has been proven to be a potent and promising target for cancer treatment. In case of prostate cancer, we once showed that antineoplastic activity of Plk1 inhibitor is largely due to inhibition of androgen receptor (AR) signaling. However, we also discovered that Plk1 inhibition causes activation of the β-catenin pathway and increased expression of c-MYC, eventually resulting in resistance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Several studies have proved that BRD4 inhibitors and PLK1 inhibitors can inhibit tumor growth in CRPC xenograft mouse models by regulate the function of AR and MYC (20,27,45). And the combination study of PLK1 inhibitor GSK461364A and BRD4 inhibitor JQ1 reported recently further demonstrated the advantages of targeting at BRD4 and PLK1 in CRPC simultaneously (28). Recently, several dual BRD4/PLK1 inhibitors with similar potency against BRD4 and PLK1 have been disclosed and they displayed potent anti-proliferation activity on AML cells (32,46), while their anti-tumor activity against CRPC has not been investigated.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have proved that BRD4 inhibitors and PLK1 inhibitors can inhibit tumor growth in CRPC xenograft mouse models by regulate the function of AR and MYC (20,27,45). And the combination study of PLK1 inhibitor GSK461364A and BRD4 inhibitor JQ1 reported recently further demonstrated the advantages of targeting at BRD4 and PLK1 in CRPC simultaneously (28). Recently, several dual BRD4/PLK1 inhibitors with similar potency against BRD4 and PLK1 have been disclosed and they displayed potent anti-proliferation activity on AML cells (32,46), while their anti-tumor activity against CRPC has not been investigated.…”
Section: Discussionmentioning
confidence: 97%
“…In TISCs, the polo-like kinase (PLK1) induces the M-phase of the cell cycle [72,73]. Studies by Mao et al, have demonstrated that the BET inhibitor produced a cell cycle arrest at G1, while the volasertib, a PLK1 inhibitor, induced cells to arrest at M-phase [74,75]. Further BET inhibitors induced not only arrest at G1-cell cycle, but also reduced the levels of kinases such as PLK1 involved in mitosis [53].…”
Section: Bet Inhibitorsmentioning
confidence: 99%
“…One of the most popular inhibitors is JQ1, a thieno diazepine-based small molecule, which shows excellent inhibition against the BET subfamily in the low nanomolar range, and is especially effective against BRD4 [74] . Currently, at least 10 BET inhibitors (BETis) have participated in clinical trials [Table 1] [75][76][77][78][79][80] . It is well reported that PCa-associated SPOP mutations cause resistance to BETis via BRD4 accumulation [77] .…”
Section: Brd4mentioning
confidence: 99%
“…It is well reported that PCa-associated SPOP mutations cause resistance to BETis via BRD4 accumulation [77] . In this regard, besides small-molecule inhibitors, a serial of proteolysis targeting chimera (PROTAC) has recently been developed to target BET proteins for degradation [78,79] . Pawar et al [71] found that PROTAC-BETd (ZBC260) effectively induces BRD4 degradation and results in BETi-resistant cells revers into sensitive cells to BETis.…”
Section: Brd4mentioning
confidence: 99%